2011
DOI: 10.1177/0017896911411761
|View full text |Cite
|
Sign up to set email alerts
|

Clustering of risk behaviours among African American adults

Abstract: Objectives: Individuals may engage in more than one risk behaviour at any given time. The extent to which risk behaviours cluster among African American adults has been largely unexplored. This study examined the prevalence and clustering of three risk behaviours among African American church members: smoking; low moderate-to-vigorous intensity leisure time physical activity (leisure MVPA); and low fruit and vegetable consumption. Design: Cross-sectional study. Setting: African Methodist Episcopal churches in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
12
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 34 publications
(54 reference statements)
5
12
0
Order By: Relevance
“…Similar to our predictor findings, cross-sectional studies have found a positive association between fruit and vegetable consumption, social support 23,25 , and exercise 25,26 in African Americans. There is cross-sectional evidence that risk behaviors, namely physical activity and fruit and vegetable consumption, may cluster in such a way that individuals with low physical activity also have low fruit and vegetable intake 55 . Perhaps engaging in one healthy behavior (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to our predictor findings, cross-sectional studies have found a positive association between fruit and vegetable consumption, social support 23,25 , and exercise 25,26 in African Americans. There is cross-sectional evidence that risk behaviors, namely physical activity and fruit and vegetable consumption, may cluster in such a way that individuals with low physical activity also have low fruit and vegetable intake 55 . Perhaps engaging in one healthy behavior (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…The selection of lifestyle behaviours has varied in both the international [8,[14][15][16][17] and national [12,13] clustering literature. Nonetheless, most of the lifestyle behaviours investigated in these studies were chosen due to their explicit associations with chronic disease (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, most of the lifestyle behaviours investigated in these studies were chosen due to their explicit associations with chronic disease (e.g. lack of physical activity, inadequate fruit and vegetable intake, alcohol consumption, and smoking) [8,[12][13][14][15][16][17]. Few studies have, however, explored the clustering of other lifestyle behaviours-including sedentary behaviour, sleep, or sugar consumption-which are not only associated with health [18][19][20] but also wellbeing [5,21].…”
Section: Introductionmentioning
confidence: 99%
“…lack of PA, poor nutrition, tobacco use, excessive alcohol consumption) are responsible for a majority of chronic diseases 5 , and often times, risk behaviors cluster 6,7 . Bambs and colleagues 8 found that only 1.4% of African Americans in their sample met the American Heart Association Ideal Health Behavior Index, defined as being a non-smoker, having a body mass index (BMI) <25 kg/m 2 , being very physically active, and consuming ≥3 fruits and vegetables per day.…”
Section: Introductionmentioning
confidence: 99%
“…PA) are more likely to engage in the other (i.e. favorable dietary behaviors) 7,1215 . Because these behaviors are often related, it seems reasonable to believe that individuals changing one behavior may also try to change the other.…”
Section: Introductionmentioning
confidence: 99%